The analysis and valuation of tax profit potential of region - V. B. Dubkova (Вестник Северо-Кавказского федерального университета)
It is considered the theoretical and practical question of analysis and valuation of tax profit potential of region and enterprises the branch of economy on its territory. The definition of production, economic, financial and tax potential in an economic category are offered and quote the opinions of specialists on questions under consideration. The communication of tax, production, economic, financial potential are analysed. The methods of factor analysis and calculation reserves of increase in profit as basis of taxation are offered and their quatitative valuation for Stavropol region are determined. The necessity of employment the differentiated method of enterprises tax profit are substantiated. Value increase of labor productivity in increase the taxable profit is proved. Stimulation of action the factors of production efficiency on the basis of the profit taxation are offered.